Preparation method of high-coercivity and high-thickness neodymium-iron-boron magnet
Through the heat diffusion of the crystal industry with static pressure such as vacuum speed condensation bands, airflow grinding, magnetic field orientation, cold temperature, low temperature sintering, and heavy -duty rare earth element layer, mechanical rough crushing, hydrogen break, airflow grinding and vacuum -high -temperature sintering and other step techniques It solves the problem of high -thickness and stubborn tannin boron magnets that are difficult to prepare high -thickness, highly corrected force, and realize the preparation of high -performance, large thickness magnets.
Patent Information
- Application Number
- CN202411572827.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-06
AI Technical Summary
It is difficult to prepare high-thickness and high coercive neodymium iron boron magnets, especially magnets with special-shaped complex structures, and conventional grain boundary diffusion technology cannot be applied to magnets with thicknesses greater than 6 mm.
NdFeB alloy micro-powder is prepared using vacuum rapid condensation belt spinning technology. The powder is obtained through an airflow mill process, and then undergoes magnetic field orientation molding and cold isostatic pressing to form a green compact with a thickness of 2~6mm. Then, through vacuum low-temperature sintering and grain boundary thermal diffusion treatment of the heavy rare earth element layer, followed by mechanical coarse crushing, hydrogen crushing and jet milling processes, fine-grained powder is obtained. Finally, vacuum high-temperature sintering and multiple heat treatments are performed to obtain high-quality powder. High coercivity and thickness NdFeB magnets.
The high -correction and high magnetic energy accumulation of large -scale iron boron sintering magnets can be achieved, which can prepare high -performance magnets with greater thickness, break through the size restrictions of conventional crystal diffusion technology, suitable for industrialized production and achieve better economic benefits.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth permanent magnet material preparation, and specifically relates to a method for preparing a high-coercive force and high-thickness neodymium iron boron magnet. Background Art
[0002] NdFeB permanent magnet materials have the characteristics of high magnetic energy product, high remanence and high coercivity, so they are widely used in new energy vehicles, energy-saving home appliances, smart machines, wind turbines and other fields. Since the operating temperature of permanent magnet motors is usually above 150°C, the permanent magnetic properties of NdFeB magnets are prone to decline or even irreversible loss under high temperature working conditions. In order to improve the thermal stability of magnet performance, it is necessary to increase the coercivity of the magnet.
[0003] The addition of heavy rare earth elements will increase the coercivity of NdFeB magnets, but the addition of high content of heavy rare earth elements will reduce the remanence of the magnet. In addition, heavy rare earth elements are scarce in the earth's crust and are expensive. In recent years, the grain boundary diffusion technology of heavy rare earth elements has been widely used. Through grain boundary diffusion, heavy rare earth elements can be diffused into the interior of the magnet along the grain boundary. The heavy rare earth elements are distributed at the edge of the main phase grains, and at the same time, some praseodymium and neodymium elements on the surface of the grains are replaced, effectively improving the coercivity of the magnet. However, the usual grain boundary diffusion technology is only effective for thinner magnets with a thickness of less than 6 mm. The current grain boundary diffusion technology cannot be applied to magnets with a thickness greater than 6 mm.
[0004] In summary, how to prepare high-thickness, high-coercivity NdFeB magnets, especially how to prepare high-thickness, high-coercivity NdFeB magnets with special-shaped and complex structures, is still a hot issue that needs to be solved urgently. Summary of the invention
[0005] The main purpose of the present invention is to overcome the deficiencies in the prior art and solve the technical problem of preparing high-thickness, high-coercivity NdFeB magnets. The present invention provides a method for preparing high-coercivity and high-thickness NdFeB magnets, which can significantly improve the coercivity of large-block NdFeB sintered magnets while enabling the magnets to have a high magnetic energy product. Even complex and irregular structures can be realized in the second magnetic field orientation molding process by selecting a mold.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a high coercive force and high thickness NdFeB magnet comprises the following steps: S1. Using vacuum rapid solidification belt spinning technology to prepare rapid solidification flakes, and then using hydrogen decomposition process to prepare NdFeB alloy powder from the rapid solidification flakes; S2, preparing a powder by a jet milling process using the NdFeB alloy powder prepared in step S1, wherein the average particle size of the powder is 2-3 μm; S3, orienting and pressing the powder prepared in step S2 in a magnetic field, and then subjecting the powder to cold isostatic pressing to obtain a green compact with a thickness of 2 to 6 mm; S4, vacuum low-temperature sintering the green compact prepared in step S3, the sintering temperature is 900-980°C, the heat preservation time is 3-5 hours, and a low-temperature sintered green compact is obtained; lowering the sintering temperature at this stage can reduce the density of the NdFeB magnet, increase the pores and grain boundary channels inside the sintered green compact, and be more conducive to the thermal diffusion of the heavy rare earth diffusion source (heavy rare earth single substance, alloy, compound, and mixture containing heavy rare earth, etc.) in the NdFeB green compact in the subsequent step S5; S5, preparing heavy rare earth element layers on the upper and lower surfaces of the low-temperature sintered green body prepared in step S4, respectively, with the thickness of the heavy rare earth element layer on one side being 1-10 μm; S6, placing the low-temperature sintered green body containing the heavy rare earth element layer into a vacuum diffusion furnace for vacuum diffusion heat treatment, wherein the diffusion heat treatment temperature is 850-980° C. and the holding time is 3-20 hours; S7, first, mechanically coarsely crushing the sintered green body after the diffusion heat treatment; Secondly, the coarsely crushed material is subjected to a hydrogenation process to obtain alloy powder. This secondary hydrogenation process can not only prepare powder materials with a finer average particle size, but more importantly, the material is hydrogenated during the secondary hydrogenation process, that is, the NdFeB material oxidized during the preparation process of steps S5 and S6 is reduced, thereby improving the anti-oxidation ability of the NdFeB material. The secondary hydrogenation process is very effective in improving the coercive force and magnetic energy product of the final magnet, especially for the heavy rare earth layer coated and screen-printed, the effect of the secondary hydrogenation process is particularly obvious; Thirdly, lubricant, antioxidant and dispersant are added to the alloy powder after hydrogen cracking and mixed evenly to obtain a mixed material powder. For the subsequent pressing lubrication and anti-oxidation, it is necessary to add lubricant and antioxidant, and dispersant is to reduce powder agglomeration. Finally, the mixed material is subjected to a jet milling process to obtain a powder material, and the average particle size of the powder material is 3.2~6μm; In this step S7, mechanical coarse crushing is combined with the secondary hydrogen crushing process, which not only makes the grain boundary diffusion magnet pulverized again, but also produces a new superposition effect. The secondary hydrogen crushing process is more conducive to the secondary airflow grinding of fine powder, and eliminates the oxidation that may be introduced by the grain boundary diffusion process in step S6, which is ultimately beneficial to reduce the oxygen content of the magnet. The average particle size of the powder material obtained by the secondary airflow grinding process is 3.2~6μm, which can not only effectively retain the effect of the grain boundary diffusion of heavy rare earth elements, so that the diffusion effect of heavy rare earth elements can be better continued, but also makes the heavy rare earth element deposits that may exist on the surface of the sintered body after the initial diffusion dispersed and wrapped on the particle surface again, so that the heavy rare earth source can be fully utilized. On the basis of the above, the secondary airflow grinding process also realizes the further refinement of the magnet particles, providing preparation for the subsequent sintering to prepare high-density magnets; The average particle size of the powder material after the secondary airflow milling of the present invention is 3.2-6 μm, which refines the particles and prepares for the subsequent step S8 powder secondary molding and step S10 high-density sintering. The control of the average particle size of the powder material after the secondary airflow milling also considers the balance of the inheritance of the fine structure after the grain boundary diffusion and the high-density sintering. S8, placing the powder material prepared in step S7 into a magnetic field for orientation and compaction, and then subjecting it to cold isostatic pressing to obtain a high-thickness compact; S9, placing the high-thickness pressed green sheet prepared in step S8 into a vacuum sintering furnace for vacuum low-temperature heat treatment, wherein the vacuum low-temperature heat treatment temperature is 400-450°C and the holding time is 0.5-1 hour; in this step S9, the lubricant, antioxidant and dispersant added in step S7 can be discharged from the magnet; S10, vacuum high-temperature sintering the high-thickness pressed green body after vacuum low-temperature heat treatment in step S9, the sintering temperature is 1020~1060°C, the heat preservation time is 1.5~5 hours, and after naturally cooling to 900°C, liquid argon is filled in for cooling to obtain a high-temperature sintered green body; the high-temperature sintering in step S10 again adjusts the distribution state of heavy rare earth elements around the grain boundaries, and also causes the heavy rare earth elements diffused into the grain boundaries to enter the main phase lattice, which is beneficial to further increase the coercive force. On this basis, on the one hand, since the heavy rare earth elements further enter the lattice to form a new 2:14:1 phase replacing praseodymium and neodymium, the saturation magnetization intensity will be reduced, so that the remanence of the magnet will be reduced; on the other hand, high temperature sintering is conducive to the formation of high-density sintered magnets, which can effectively reduce void defects and help increase the remanence of the magnet; so considering the above, the high temperature sintering temperature should not be too high or too low, and needs to be specially set to 1020~1060°C. More preferably, for cerium-containing magnets, sintering at 1020~1040°C can be adopted, and for cerium-free magnets, sintering at 1030~1060°C can be adopted; S11, subjecting the high-temperature sintered green body obtained in step S10 to a vacuum primary heat treatment at a temperature of 800-920° C., keeping the temperature for 1.5-5 hours, and then filling with liquid argon gas for cooling; S12, subjecting the high temperature sintered green body after the vacuum primary heat treatment in step S11 to vacuum secondary heat treatment at a temperature of 450-650°C, keeping the temperature for 1.5-3 hours, then filling with liquid argon for cooling, and taking out of the furnace to obtain a high coercive force and high thickness NdFeB magnet.
[0007] Furthermore, in the step S1, the NdFeB alloy powder is a single alloy powder, or a mixed alloy powder consisting of a main alloy powder and a supplementary alloy powder.
[0008] Furthermore, in the step S5, the heavy rare earth element layer is prepared by coating, immersion, sputtering, screen printing, evaporation or electroplating.
[0009] Furthermore, in step S5, the material of the heavy rare earth element layer is a heavy rare earth element, a heavy rare earth alloy, a heavy rare earth compound or a mixture of heavy rare earth elements.
[0010] Furthermore, the heavy rare earth element is Dy, Tb or Ho.
[0011] Furthermore, in the step S8, the thickness of the high-thickness green compact is determined according to the design dimensions of the compacting mold and the compacting process.
[0012] The beneficial effects of the present invention are: First, the green compact (thickness 2-6 mm) is obtained by rapid solidification belt spinning, hydrogen crushing, air flow grinding (average particle size controlled at 2-3 microns), magnetic field orientation molding, and cold isostatic pressing. The green compact is subjected to vacuum low-temperature sintering (900-980°C) to obtain a low-temperature sintered green body. Secondly, a heavy rare earth element layer is prepared on the upper and lower surfaces of the low-temperature sintered green body, and then a grain boundary thermal diffusion treatment (850-980°C) is performed. Thirdly, the low-temperature sintered green body after the grain boundary diffusion heat treatment is subjected to mechanical coarse crushing, hydrogen crushing, and powder mixing (adding lubricants, antioxidants, etc.) agent and dispersant), and then jet milling to obtain powder material (average particle size of 3.2~6μm); finally, the powder material obtained by jet milling is placed in a magnetic field for orientation molding, and is subjected to cold isostatic pressing to obtain a high-thickness compact, which is sequentially subjected to vacuum low-temperature heat treatment (400~450°C), vacuum high-temperature sintering (1020~1060°C), vacuum primary heat treatment (800~920°C), and vacuum secondary heat treatment (450~650°C) to obtain a high-coercivity and high-thickness NdFeB magnet. The present invention breaks through the limitation of conventional grain boundary diffusion technology on the size of NdFeB magnets, and realizes the preparation of high-thickness NdFeB magnets with high coercivity in the magnetization direction. The present invention is easy to operate, has obvious advantages, is suitable for industrial production, and can achieve good economic benefits. DETAILED DESCRIPTION
[0013] The present invention is further described in detail below in conjunction with embodiments. Example 1
[0014] A method for preparing a high coercive force and high thickness NdFeB magnet comprises the following steps: S1. Weigh the raw materials according to the composition and proportion of the NdFeB magnet. The chemical formula of the NdFeB magnet in this embodiment 1 is (PrNd) 30 Cu 0.25 Co 0.25 Al 0.2 Ga 0.25 Zr 0.2 B 0.88 Fe 67.97 , using vacuum rapid solidification spinning belt technology to prepare rapid solidification flakes, and then using hydrogen decomposition process to prepare NdFeB alloy powder; S2, preparing a powder by jet milling the NdFeB alloy powder prepared in step S1, wherein the average particle size of the powder is 2.8 μm; S3, orienting and pressing the powder prepared in step S2 in a magnetic field, and then subjecting it to cold isostatic pressing to obtain a green compact with a thickness of 4 mm; S4, vacuum sintering the green compact prepared in step S3 at a low temperature, the sintering temperature is 900° C., and the holding time is 3 hours to obtain a low-temperature sintered green compact; S5, using a sputtering process to prepare a heavy rare earth element Tb layer on the upper and lower surfaces of the low-temperature sintered green body prepared in step S4, respectively, and the thickness of the single-sided heavy rare earth element layer is 3 μm; S6, placing the low-temperature sintered green body containing the heavy rare earth element layer into a vacuum diffusion furnace for vacuum diffusion heat treatment, the diffusion heat treatment temperature is 900° C., and the holding time is 15 hours; S7. First, the sintered green body after diffusion heat treatment is mechanically coarsely crushed; secondly, the coarsely crushed material is subjected to a hydrogen crushing process to obtain alloy powder; thirdly, 1wt% lubricant (tributyl borate), 1.5wt% antioxidant (a mixture of organic lipids and aviation gasoline), and 0.6wt% dispersant (polyethylene glycol) are added to the hydrogen-crushed alloy powder and mixed evenly to obtain a mixed material powder; finally, the mixed material powder is subjected to a jet milling process to obtain a powder material, and the average particle size of the powder material is 3.3μm; S8, placing the powder material prepared in step S7 into the magnetic field again for orientation and pressing, determining the thickness of the high-thickness green compact according to the design size of the pressing mold and the pressing process, and then subjecting the green compact to cold isostatic pressing to obtain a high-thickness green compact with a thickness of 35 mm; S9, placing the high-thickness pressed green sheet prepared in step S8 into a vacuum sintering furnace for vacuum low-temperature heat treatment, wherein the vacuum low-temperature heat treatment temperature is 400° C. and the holding time is 1 hour; S10, vacuum high-temperature sintering the high-thickness pressed green body after vacuum low-temperature heat treatment in step S9, the sintering temperature is 1040°C, the heat preservation time is 3 hours, and after natural cooling to 900°C, liquid argon is filled in for cooling to obtain a high-temperature sintered green body; S11, subjecting the high-temperature sintered green body prepared in step S10 to a vacuum primary heat treatment at a temperature of 880°C, keeping the temperature for 2 hours, and then filling with liquid argon for cooling; S12, the sintered green body after the vacuum primary heat treatment in step S11 is subjected to vacuum secondary heat treatment at a temperature of 560°C, kept at this temperature for 2 hours, then filled with liquid argon for cooling, and taken out of the furnace to obtain a high coercive force and high thickness NdFeB magnet. The room temperature performance of the high coercive force and high thickness NdFeB magnet prepared in this embodiment 1 is: remanence Br=14.0 kGs, maximum magnetic energy product (BH)max=48MGOe, intrinsic coercive force Hcj=24.2 kOe. Example 2
[0015] A method for preparing a high coercive force and high thickness NdFeB magnet. The remaining steps and process parameters of Example 2 are the same as those of Example 1, except that the target material used in the sputtering process in step S5 is Dy 70 Cu 20 Al8Ga2, the room temperature performance of the high coercive force and high thickness NdFeB magnet prepared in Example 2 is: remanence Br=13.98 kGs, maximum magnetic energy product (BH)max=46.8 MGOe, intrinsic coercive force Hcj=19.8 kOe. Example 3
[0016] A method for preparing a high coercive force and high thickness NdFeB magnet comprises the following steps: S1. Weigh the raw materials according to the composition and proportion of the NdFeB magnet. The chemical formula of the NdFeB magnet in this embodiment 3 is: (PrNd) 30 Cu 0.25 Co 0.25 Al 0.2 Ga 0.25 Zr 0.2 B 0.88 Fe 67.97 , using vacuum rapid solidification spinning belt technology to prepare rapid solidification flakes, and then using hydrogen decomposition process to prepare NdFeB alloy powder; S2, preparing a powder by a jet milling process using the NdFeB alloy powder prepared in step S1, wherein the average particle size of the powder is 3 μm; S3, orienting and pressing the powder prepared in step S2 in a magnetic field, and then subjecting it to cold isostatic pressing to obtain a green compact with a thickness of 4 mm; S4, vacuum sintering the green compact prepared in step S3 at a low temperature, the sintering temperature is 950° C., and the holding time is 3 hours to obtain a low-temperature sintered green compact; S5, applying a TbH2 ethanol-based solution with a thickness of 2 μm on the upper and lower surfaces of the low-temperature sintered green body prepared in step S4, and drying to obtain a heavy rare earth element TbH2 layer on the upper and lower surfaces of the low-temperature sintered green body; S6, placing the low-temperature sintered green body containing the heavy rare earth element layer into a vacuum diffusion furnace for vacuum diffusion heat treatment, the diffusion heat treatment temperature is 900° C., and the holding time is 15 hours; S7. First, the sintered green body after diffusion heat treatment is mechanically coarsely crushed; secondly, the coarsely crushed material is subjected to a hydrogen crushing process to obtain alloy powder; thirdly, 1.5wt% lubricant (tributyl borate), 2wt% antioxidant (a mixture of organic lipids and aviation gasoline), and 0.8wt% dispersant (polyethylene glycol) are added to the hydrogen-crushed alloy powder and mixed evenly to obtain a mixed material powder; finally, the mixed material powder is subjected to a jet milling process to obtain a powder material, and the average particle size of the powder material is 3.4μm; S8, placing the powder material prepared in step S7 into the magnetic field again for orientation and pressing, determining the thickness of the high-thickness green compact according to the design size of the pressing mold and the pressing process, and then subjecting the green compact to cold isostatic pressing to obtain a high-thickness green compact with a thickness of 35 mm; S9, placing the high-thickness pressed green sheet prepared in step S8 into a vacuum sintering furnace for vacuum low-temperature heat treatment, wherein the vacuum low-temperature heat treatment temperature is 420° C. and the holding time is 1 hour; S10, vacuum high-temperature sintering the high-thickness pressed green body after vacuum low-temperature heat treatment in step S9, the sintering temperature is 1040° C., the heat preservation time is 2 hours, and after natural cooling to 900° C., liquid argon is filled in for cooling to obtain a high-temperature sintered green body; S11, subjecting the high-temperature sintered green body prepared in step S10 to a vacuum primary heat treatment at a temperature of 900° C., keeping the temperature for 2 hours, and then filling with liquid argon gas for cooling; S12, subjecting the sintered green body after the primary vacuum heat treatment in step S11 to secondary vacuum heat treatment at a temperature of 600°C, keeping the temperature for 3 hours, then filling with liquid argon to cool it, and taking it out of the furnace to obtain a high coercive force and high thickness NdFeB magnet. The room temperature performance of the high coercive force and high thickness NdFeB magnet prepared in this embodiment 3 is: remanence Br=13.8 kGs, maximum magnetic energy product (BH)max=47MGOe, intrinsic coercive force Hcj=23.4 kOe. Example 4
[0017] A method for preparing a high coercive force and high thickness NdFeB magnet, the remaining steps and process parameters of this embodiment 4 are the same as those of embodiment 3, and the only difference is step S5: immersing the sintered body prepared in step S4 in an ethanol-based suspension solution of DyH2+ nano-Cu, and preparing a heavy rare earth element DyH2+ nano-Cu layer on the upper and lower surfaces of the sintered body after drying. The room temperature performance of the high coercive force and high thickness NdFeB magnet prepared in this embodiment 4 is: remanence Br=13.5 kGs, maximum magnetic energy product (BH)max=45MGOe, intrinsic coercive force Hcj=17.9 kOe. Example 5
[0018] A method for preparing a high coercive force and high thickness NdFeB magnet. The remaining steps and process parameters of Example 5 are the same as those of Example 3, and the only difference is that step S5: the sintered green body prepared in step S4 is printed by screen printing. 70 Cu 20 Ga 10 The powder, resin binder and anhydrous ethanol are mixed to form a slurry. The room temperature performance of the high coercivity and high thickness NdFeB magnet prepared in Example 5 is: remanence Br = 13.7 kGs, maximum magnetic energy product (BH) max = 46 MGOe, intrinsic coercivity Hcj = 22 kOe. Comparative Example 1
[0019] Preparation of NdFeB Alloy (PrNd) by Vacuum Rapid Solidification Spinning Technology 30 Cu 0.25 Co 0.25 Al 0.2 Ga 0.25 Zr 0.2 B 0.88 Fe 67.97 Rapidly solidify the flakes, and prepare the NdFeB alloy powder by hydrogen breaking process; powder is made by air flow milling process, and the average particle size is 2.8 microns; then add an appropriate amount of 1wt% lubricant (tributyl borate), 1.5wt% antioxidant (mixture of organic lipids and aviation gasoline), and 0.6wt% dispersant (polyethylene glycol) to the powder for 2h; then press and form in magnetic field, and obtain a 35 mm thick pressed green sheet after cold isostatic pressing; then sinter at 1070°C high temperature vacuum, keep warm for 3 hours; then vacuum heat treatment at 880°C, keep warm for 2 hours, and then fill with room temperature argon to cool; then vacuum heat treatment at 560°C, keep warm for 2 hours, and then fill with room temperature argon to cool. The room temperature performance of the sintered NdFeB magnet obtained in this comparative example 1 is: remanence Br=14.2 kGs, maximum magnetic energy product (BH)max=50 MGOe, intrinsic coercivity Hcj=14.6 kOe.
[0020] The initial NdFeB composition of Examples 1 to 5 and Comparative Example 1 is the same, and Comparative Example 1 is a conventional sintered magnet. By comparing Examples 1 to 5 with Comparative Example 1, it can be found that the present invention can prepare high-performance and large-thickness magnets. The remanence and magnetic energy product of the magnet of the present invention are slightly lower than those of the conventional sintered magnet, but the intrinsic coercive force of the magnet is significantly improved. Example 6
[0021] A method for preparing a high coercive force and high thickness NdFeB magnet comprises the following steps: S1. Weigh the raw materials according to the composition and proportion of the NdFeB magnet. The chemical formula of the NdFeB magnet in this embodiment 6 is (PrNd) 30.2 Cu 0.22 Co 0.25 Al 0.2 Ga 0.1 B 0.9 Fe 68.13 , using vacuum rapid solidification spinning belt technology to prepare rapid solidification flakes, and then using hydrogen decomposition process to prepare NdFeB alloy powder; S2, preparing a powder by a jet milling process using the NdFeB alloy powder prepared in step S1, wherein the average particle size of the powder is 3 μm; S3, orienting and pressing the powder prepared in step S2 in a magnetic field, and then subjecting it to cold isostatic pressing to obtain a green compact with a thickness of 5 mm; S4, vacuum sintering the green compact prepared in step S3 at a low temperature, the sintering temperature is 980° C., and the holding time is 5 hours to obtain a low-temperature sintered green compact; S5, immersing the low-temperature sintered green body prepared in step S4 in an ethanol-based suspension solution of TbH2+ nano-Cu, and preparing a heavy rare earth element TbH2+ nano-Cu layer on the upper and lower surfaces of the low-temperature sintered green body after drying, wherein the thickness of the single-sided heavy rare earth element TbH2+ nano-Cu layer is 3 μm; S6, placing the low-temperature sintered green body containing the heavy rare earth element layer into a vacuum diffusion furnace for vacuum diffusion heat treatment, the diffusion heat treatment temperature is 910° C., and the holding time is 5.5 hours; S7. First, the sintered green body after diffusion heat treatment is mechanically coarsely crushed; secondly, the coarsely crushed material is subjected to a hydrogen crushing process to obtain alloy powder; thirdly, 1.5wt% lubricant (tributyl borate), 1.5wt% antioxidant (a mixture of organic lipids and aviation gasoline), and 0.5wt% dispersant (polyethylene glycol) are added to the hydrogen-crushed alloy powder and mixed evenly to obtain a mixed material powder; finally, the mixed material powder is subjected to a jet milling process to obtain a powder material, and the average particle size of the powder material is 3.8μm; S8, placing the powder material prepared in step S7 into the magnetic field again for orientation and pressing, determining the thickness of the high-thickness green compact according to the design size of the pressing mold and the pressing process, and then subjecting the green compact to cold isostatic pressing to obtain a high-thickness green compact with a thickness of 30 mm; S9, placing the high-thickness pressed green sheet prepared in step S8 into a vacuum sintering furnace for vacuum low-temperature heat treatment, wherein the vacuum low-temperature heat treatment temperature is 460° C. and the holding time is 1.5 hours; S10, vacuum high-temperature sintering the high-thickness pressed green body after vacuum low-temperature heat treatment in step S9, the sintering temperature is 1030° C., the heat preservation time is 1 hour, and after natural cooling to 900° C., liquid argon is filled in for cooling to obtain a high-temperature sintered green body; S11, subjecting the high-temperature sintered green body prepared in step S10 to a vacuum primary heat treatment at a temperature of 850°C, keeping the temperature for 2 hours, and then filling with liquid argon for cooling; S12, subjecting the sintered green body after the primary vacuum heat treatment in step S11 to a secondary vacuum heat treatment at a temperature of 620°C, keeping the temperature for 2 hours, then filling with liquid argon to cool, and taking it out of the furnace to obtain a high coercive force and high thickness NdFeB magnet. The room temperature properties of the high coercive force and high thickness NdFeB magnet prepared in Example 6 are: remanence Br=13.5 kGs, maximum magnetic energy product (BH)max=45.3 MGOe, intrinsic coercive force Hcj=19.1 kOe. Comparative Example 2
[0022] Preparation of NdFeB Alloy (PrNd) by Vacuum Rapid Solidification Spinning Technology 30.2 Cu 0.22 Co 0.25 Al 0.2 Ga 0.1 B 0.9 Fe 68.13 Rapidly solidify the scales, and prepare the NdFeB alloy powder by hydrogen breaking process; powder is made by air flow milling process, and the average particle size is 3.2 microns; then add an appropriate amount of 1wt% lubricant (tributyl borate), 1.5wt% antioxidant (mixture of organic lipids and aviation gasoline), and 0.6wt% dispersant (polyethylene glycol) to the powder for 2h; then press and form in magnetic field, and obtain a 35 mm thick pressed green sheet after cold isostatic pressing; then sinter at 1070°C high temperature vacuum, keep warm for 1 hour; then vacuum heat treatment at 850°C, keep warm for 2 hours, and then fill with room temperature argon to cool; then vacuum heat treatment at 620°C, keep warm for 2 hours, and then fill with room temperature argon to cool. The room temperature performance of the sintered NdFeB magnet obtained in this comparative example 2 is: remanence Br=13.9 kGs, maximum magnetic energy product (BH)max=47MGOe, intrinsic coercivity Hcj=12.5 kOe.
[0023] Comparative Example 2 is a conventional sintered magnet. The NdFeB alloy composition of Example 6 and Comparative Example 2 is the same. By comparing the two, it can be found that the present invention can prepare high-performance and thick magnets. The remanence and magnetic energy product of the magnet of the present invention are slightly lower than those of the conventional sintered magnet, but the intrinsic coercive force of the magnet is significantly improved.
[0024] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing a high coercive force and high thickness NdFeB magnet, characterized in that: The following steps are involved: S1. Using vacuum rapid solidification belt spinning technology to prepare rapid solidification flakes, and then using hydrogen decomposition process to prepare NdFeB alloy powder from the rapid solidification flakes; S2, preparing a powder by a jet milling process using the NdFeB alloy powder prepared in step S1, wherein the average particle size of the powder is 2-3 μm; S3, orienting and pressing the powder prepared in step S2 in a magnetic field, and then subjecting the powder to cold isostatic pressing to obtain a green compact with a thickness of 2 to 6 mm; S4, vacuum sintering the green compact prepared in step S3 at a low temperature, the sintering temperature being 900-980° C., and the holding time being 3-5 hours, to obtain a low-temperature sintered green compact; S5, preparing heavy rare earth element layers on the upper and lower surfaces of the low-temperature sintered green body prepared in step S4, respectively, with the thickness of the heavy rare earth element layer on one side being 1-10 μm; S6, placing the low-temperature sintered green body containing the heavy rare earth element layer into a vacuum diffusion furnace for vacuum diffusion heat treatment, wherein the diffusion heat treatment temperature is 850-980° C. and the holding time is 3-20 hours; S7, firstly, mechanically coarsely crushing the sintered green body after diffusion heat treatment; secondly, the coarsely crushed material is subjected to hydrogen crushing process to obtain alloy powder; thirdly, lubricant, antioxidant and dispersant are added to the hydrogen crushed alloy powder and mixed evenly to obtain mixed material powder; finally, the mixed material powder is subjected to air flow milling process to obtain powder material, and the average particle size of the powder material is 3.2~6μm; S8, placing the powder material prepared in step S7 into the magnetic field again for orientation and compaction, and then subjecting it to cold isostatic pressing to obtain a high-thickness compact; S9, placing the high-thickness pressed green sheet prepared in step S8 into a vacuum sintering furnace for vacuum low-temperature heat treatment, wherein the vacuum low-temperature heat treatment temperature is 400-450° C. and the holding time is 0.5-1 hour; S10, vacuum high-temperature sintering the high-thickness pressed green body after vacuum low-temperature heat treatment in step S9, the sintering temperature is 1020-1060°C, the heat preservation time is 1.5-5 hours, and after naturally cooling to 900°C, liquid argon is filled in for cooling to obtain a high-temperature sintered green body; S11, subjecting the high-temperature sintered green body prepared in step S10 to a vacuum primary heat treatment at a temperature of 800-920° C., keeping the temperature for 1.5-5 hours, and then filling with liquid argon gas for cooling; S12, subjecting the high temperature sintered green body after the vacuum primary heat treatment in step S11 to vacuum secondary heat treatment at a temperature of 450-650°C, keeping the temperature for 1.5-3 hours, then filling with liquid argon for cooling, and taking out of the furnace to obtain a high coercive force and high thickness NdFeB magnet.
2. The method for preparing a high coercive force and high thickness NdFeB magnet according to claim 1, characterized in that: In the step S1, the NdFeB alloy powder is a single alloy powder, or a mixed alloy powder consisting of a main alloy powder and an auxiliary alloy powder.
3. The method for preparing a high coercive force and high thickness NdFeB magnet according to claim 1, characterized in that: In the step S5, the heavy rare earth element layer is prepared by coating, immersion, sputtering, screen printing, evaporation or electroplating.
4. The method for preparing a high coercive force and high thickness NdFeB magnet according to claim 1 or 3, characterized in that: In the step S5, the material of the heavy rare earth element layer is a heavy rare earth element, a heavy rare earth alloy, a heavy rare earth compound or a mixture of heavy rare earth elements.
5. The method for preparing a high coercive force and high thickness NdFeB magnet according to claim 4, characterized in that: The heavy rare earth element is Dy, Tb or Ho.
6. The method for preparing a high coercive force and high thickness NdFeB magnet according to claim 1, characterized in that: In step S8, the thickness of the high-thickness green compact is determined according to the design dimensions of the compacting mold and the compacting process.
Citation Information
Patent Citations
Rare earth permanent magnetic material and preparation method thereof
CN106782969A
Method for preparing high coercivity NdFeB magnets containing less heavy rare earth
CN106783128A
Preparation method of low-heavy-rare-earth and high-coercivity neodymium iron boron magnet
CN107546027A
Preparation process of rare earth neodymium iron boron permanent magnet with low heavy rare earth content and high coercivity
CN114864264A
Preparation method of efficient rare earth bonded permanent magnet
CN118053666A